Fatores que afetam o clima da escola: a visão dos professores - Miranda, Antônio Carlos; Bertagna, Regiane Helena; Freitas, Luiz Carlos De (UNICAMP - Faculdade de Educação, 2019)
Abstract The goal of this study is to analyze the factors that, thought the teachers' vision, can affect the development of the school climate, based on longitudinal study of School Generation Project (Geres), started in 2005, where the same schools and students samples were observed during four years. The sample had 312 basic level schools in five Brazilian cities and at the end of collecting data registered 35.538 students, 2918 teachers and 669 directors. Faccenda, Dalben and Freitas provided to this study all selected variables to compound the school climate indicator. The results showed that the evaluation of the public schools teachers related to the influence of external factor in their schools is up to three times higher than in private and special schools. indicating the violence among students, the interference of drug trafficking as factors that tend to influence negatively the school climate.

Resumo Este artigo analisa os fatores que, na visão dos professores, afetam o clima escolar, a partir de dados do estudo longitudinal do Projeto Geres, iniciado em 2005, que observou durante quatro anos a mesma amostra de escolas e alunos. A amostra contemplou 312 instituições de ensino fundamental em cinco cidades, que ao final da coleta, em 2008, registrava 35.538 alunos, 2.918 professores e 669 diretores. Faccenda, Dalben e Freitas forneceram a este trabalho a base para a escolha das variáveis que formaram o construto do indicador de clima escolar. Os resultados mostraram que a avaliação dos professores das redes municipais e estaduais sobre a influência dos fatores externos em suas escolas é até três vezes maior do que na rede especial e privada, apontando a violência entre alunos e a interferência do tráfico de drogas como possíveis influências negativas no ambiente da escola.
Factors which influence the school climate in the teachers’ vision
Keywords: school climate; teacher; public and private schools; longitudinal study; clima escolar; professores; redes de ensino; estudo longitudinal